The Urban Quilombo of Cracolândia - Guatteri, Guglielmo (Lidé města, 2025)
This text offers a political reading of the Cracolândia neighborhood in São Paulo, Brazil. As one of the largest areas of drug trafficking and consumption in the world, this urban area is marked by immense violence, driven by the state’s actions against it and then daily incorporated within it. The aim is to contextualize this violence within the broader dynamics of governance in the Brazilian state, particularly through the lens of race. Following the insights of anthropologist Amanda Amparo, this paper proposes expanding the concept of Cracolândia as an Urban Quilombo: a technique through which a Black population seeks to escape the death policies imposed by a racist power structure. Compared with Amparo’s work, this article emphasizes the political – both practical and symbolic – importance of Cracolândia’s spatial location, not in a peripheral area or favela, but in the very heart of the city.